2021
DOI: 10.3390/microorganisms9081698
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Bacterial Strains for Control of Root-Knot Disease Caused by Meloidogyne incognita

Abstract: Root-knot disease caused by Meloidogyne incognita leads to significant crop yield losses that may be aggravated by the association with pathogenic fungi and bacteria. Biological agents can be effectively used against the complex disease of root-knot nematode and pathogenic fungi. In this study, 35 bacterial strains were analyzed for their in vitro nematicidal, antagonistic and growth stimulation activities. Based on results from the in vitro assays, grow-box experiments on tomato and cucumber were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Furthermore, some B. velezensis strains encoded lignocellulolytic enzymes and exhibited the potential for degrading lignocellulosic biomass [33]. In addition, B. velezensis BZR 86 significantly controlled the root-knot disease on plants and noticeably increased growth and biomass of plants [34]. It was reported that bacterial treatment with B. velezensis YC7010 elicited the induced systemic resistance (ISR) and noticeably decreased settling, feeding, and reproduction of green peach aphid on Arabidopsis leaves [35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some B. velezensis strains encoded lignocellulolytic enzymes and exhibited the potential for degrading lignocellulosic biomass [33]. In addition, B. velezensis BZR 86 significantly controlled the root-knot disease on plants and noticeably increased growth and biomass of plants [34]. It was reported that bacterial treatment with B. velezensis YC7010 elicited the induced systemic resistance (ISR) and noticeably decreased settling, feeding, and reproduction of green peach aphid on Arabidopsis leaves [35].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, genera Arthrobacter , Bacillus , and Chujaibacter decreased their abundance. Bacillus bacteria shows significant anti-nematode activity by producing plantazolicin (such as B. amyloliquefaciens FZB42) or inducing systemic resistance in plants (such as B. atrophaeus GBSC56) ( Liu et al, 2013 ; Xiong et al, 2015 ; Cheng et al, 2020 ; Ayaz et al, 2021 ; Migunova et al, 2021 ; Yin et al, 2021 ). Moreover, Bacillus colonization was negatively correlated with pathogen abundance and disease incidence ( Xue et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Culture supernatant of Streptomyces hydrogenans DH-16 lowers the root galls in the infested plants by M. incognita and promotes the growth of Solanum lycopersicum seedlings ( Sharma et al, 2020 ). The application of B. velezensis BZR 86 significantly decreases the development of root-knot disease in tomato and cucumber vegetables ( Migunova et al, 2021 ). Pot experiment suggested that Pseudomonas simiae strain MB751 exhibits significant nematicidal activity against M. incognita with approximately 80% mortality toward pre-parasitic second stage juveniles (pre-J2s; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments of potato plants with a recombinant B. subtilis strain, which secreted plant-defense elicitor peptide StPep1, effectively reduced root galling caused by Meloidogyne chitwoodi [ 68 ]. The treatment of cucumber and tomato plants with Bacillus velezensis BZR 86 significantly reduced the development of root-knot disease caused by M. incognita , and, as a result, the growth of the plants was enhanced [ 69 ].…”
Section: Control Strategies For Rknsmentioning
confidence: 99%